2013
DOI: 10.1261/rna.037531.112
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the binding specificity of the RNA-binding protein GLD-1 suggests a function of coding region–located sites in translational repression

Abstract: To understand the function of the hundreds of RNA-binding proteins (RBPs) that are encoded in animal genomes it is important to identify their target RNAs. Although it is generally accepted that the binding specificity of an RBP is well described in terms of the nucleotide sequence of its binding sites, other factors such as the structural accessibility of binding sites or their clustering, to enable binding of RBP multimers, are also believed to play a role. Here we focus on GLD-1, a translational regulator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…4A,B; Abdelmohsen et al 2011;Darnell et al 2011;Cho et al 2012;Brummer et al 2013). To determine whether Unkempt associates with polyribosomes, we fractionated the lysates of SH-SY5Y cells and mouse embryonic brains on linear sucrose density gradients and examined the sedimentation pattern of Unkempt ( Fig.…”
Section: Unkempt Reduces Translational Efficiency Of Target Mrnasmentioning
confidence: 99%
“…4A,B; Abdelmohsen et al 2011;Darnell et al 2011;Cho et al 2012;Brummer et al 2013). To determine whether Unkempt associates with polyribosomes, we fractionated the lysates of SH-SY5Y cells and mouse embryonic brains on linear sucrose density gradients and examined the sedimentation pattern of Unkempt ( Fig.…”
Section: Unkempt Reduces Translational Efficiency Of Target Mrnasmentioning
confidence: 99%
“…2A). This site (GMB 1) contained a sequence that matches the GLD-1-binding motif (GBM) that we inferred previously using motif-based enrichment of the reads from the HITS-CLIP experiment (Brümmer et al 2013). Inspection of an additional published data set of GLD-1-binding sites generated via photoactivatable ribonucleoside-enhanced CLIP (PAR-CLIP) (Jungkamp et al 2011) identified evidence for a second candidate GLD-1-binding site (GBM 2) 300 base pairs (bp) downstream from GBM 1 in the ced-3 3 ′ UTR ( Fig.…”
Section: Resultsmentioning
confidence: 82%
“…S4C). In order to test whether GLD-1 binds directly to the ced-3 mRNA, we reanalyzed a set of transcriptome-wide GLD-1-binding sites that we generated previously by high-throughput sequencing of RNA isolated by crosslinking and immunoprecipitation (HITS-CLIP) of a transgenic line expressing a rescuing GLD-1::STREP/HA transgene (Brümmer et al 2013). We identified an enrichment of clipped reads at one site in the ced-3 3 ′ UTR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations